Analisis Implementasi E-Filing Dalam Pembayaran Pajak Online Bagi Masyarakat Di Kota - Serli Diovani Teza; Annisa Risecha Junep (Prosiding, 2018)
The Government continues to maximize the potential of existing taxes to meet the State financing each year. One of the efforts by facilitating taxpayers to report their taxes through E-Filing or Electronic Filing System is this effort seen from the low level of individual taxpayer compliance due to taxpayers who have enrolled but not reported the SPT. The purpose of this research is to know the improvement of tax compliance report of Individual Personal Tax Payer in front of E-Filing as well as the factors that become obstacles in the implementation of E-Filing. This research includes descriptive research type using qualitative approach. Population in this research is all personal tax payer in Batam city, The sample of research use purposive sampling. The results of this study indicate that the implementation of E-filing has been quite successful in improving compliance through increasing the rate of submission of individual taxpayer annual tax returns. So many taxpayers feel more practical, easy, fast and efficient by using e-filing. But there are some obstacles in the application of e-filing, one of the obstacles is the lack of knowledge of taxpayers and the difficulty of convincing taxpayers will use e-filing easier and more efficiently. The targeted findings are not reached, still high or above 50% of the people of Batam do not understand e-filing yet, but those who already use e-filing implementations of E-filing are quite successful in improving compliance.